Implementasi Metode MAUT Dalam Menentukan Prioritas Produk Unggulan Daerah Dengan Menerapkan Pembobotan ROC - Agung Triayudi; Jumpa Dorisman Rajagukguk; Mesran Mesran (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
As the industry grows, the competition for superior products in this region is getting tougher. This competition will force all industries to pay more attention to policy making. Decision making to prioritize the best regional products according to needs and capabilities requires accurate and effective decisions to make the right choice and minimize losses in both cost and time. With the problems mentioned above, local governments (PEMDAs) are bothered with determining the priority of regional superior products quickly and precisely. Therefore, to determine the priority of regional superior products, a decision support system is needed to facilitate work and avoid errors in calculating system data quickly and more accurately. The Rank Order Centroid (ROC) and Multi Attribute Utility Theory (MAUT) methods are a combination of methods that support in determining the priority criteria for regional superior products. The results of the application of the combination according to the formulas and methods used to obtain the highest value alternative are Coffee products with the first rank, namely 0.00653.